1997
DOI: 10.1021/ja971403a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Potential and pH Dependences of [3Fe-4S] ↔ [M3Fe-4S] Cluster Transformations (M = Fe, Zn, Co, and Cd) in Ferredoxin III from Desulfovibrio africanus and Detection of a Cluster with M = Pb

Abstract: The 7Fe ferredoxin from Desulfovibrio africanus contains a reactive 3Fe cluster which incorporates Fe and other metals to form cubanes [M3Fe-4S] having non-cysteine ligation to the added metal (M). These reactions are addressed at controlled potentials in protein molecules adsorbed on a graphite electrode, thereby facilitating an appraisal of factors that control cluster interconversions. Electrochemical and spectroscopic methods have been used to establish connectivities among interconversions with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 41 publications
1
48
1
Order By: Relevance
“…It has also been demonstrated for the [Fe-S] cluster binding protein, ferredoxin, that Zn 2C can be incorporated into these clusters. 49 Therefore, the possibility that zinc-ligation of IscU plays a physiological role cannot be ruled out. Based on the structural similarity with SufE and YgdK, the zinc-bound IscU structure appears to be a good structural model for a stabilized form of IscU.…”
Section: Discussion Zn 2c Binding May Be Similar To Fe 2c Bindingmentioning
confidence: 99%
“…It has also been demonstrated for the [Fe-S] cluster binding protein, ferredoxin, that Zn 2C can be incorporated into these clusters. 49 Therefore, the possibility that zinc-ligation of IscU plays a physiological role cannot be ruled out. Based on the structural similarity with SufE and YgdK, the zinc-bound IscU structure appears to be a good structural model for a stabilized form of IscU.…”
Section: Discussion Zn 2c Binding May Be Similar To Fe 2c Bindingmentioning
confidence: 99%
“…The pH dependence of the three redox couples measured over the pH range 5-8 was essentially identical to that of native Da FdIII [12] ; i.e. signals Ah and Bh only vary slightly with pH, whereas signal Ch shows strong pH-dependent behaviour, consistent with the two-electron reduction of [3Fe-4S]!…”
Section: Nmr Spectroscopy Of Reconstituted Ht Da Fdiiimentioning
confidence: 65%
“…FdIII has been demonstrated for M l Fe(II), Zn(II), Cd(II), Tl(I), Cu(I), Co(II) and Pb(II), using both spectroscopic studies and direct electrochemical methods [3,11,12]. When Da FdIII is adsorbed as a film on a pyrolytic graphite edge (PGE) electrode, it is capable of responding rapidly to changes in solution conditions and displays facile cluster conversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Site-directed mutagenesis has suggested that formation of the latter species requires the presence of non-ligating Cys 24 in the vicinity of a cluster sulfide (33). The difference between the oxidative degradation of ferredoxin from A. vinelandii and Sulfolobus sp.…”
Section: Oxidative Degradation Of Two Fes Clusters In Bacterial Typementioning
confidence: 99%